2012
DOI: 10.1111/j.1440-1746.2011.06978.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of tumor necrosis factor‐α gene promoter polymorphism at sites ‐308 and ‐238 with non‐alcoholic fatty liver disease: A meta‐analysis

Abstract: This meta-analysis suggested that TNF-α gene promoter polymorphism at position -238 but not -308 might be a risk factor for NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 30 publications
(62 reference statements)
0
31
0
4
Order By: Relevance
“…TNF-α polymorphisms have been shown to be strongly associated with the risk of developing NAFLD especially in Chinese population and this was confirmed in a meta-analysis by Wang et al [11].…”
Section: Introductionmentioning
confidence: 68%
“…TNF-α polymorphisms have been shown to be strongly associated with the risk of developing NAFLD especially in Chinese population and this was confirmed in a meta-analysis by Wang et al [11].…”
Section: Introductionmentioning
confidence: 68%
“…Furthermore, a recent meta-analysis has demonstrated that polymophisms of TNF-α (-238) is particularly associated with the susceptibility to NAFLD [142] . TNF-α has also been previously known to be an important cytokine that regulates insulin resistance by affecting insulin receptor substrate-1 (IRS-1) and insulin receptor kinase (IRK) in the insulin signal transduction pathway [142] . Nevertheless, the involvement of TNF-α in insulin resistance is debatable.…”
Section: Genes That Affect Cytokines Productionmentioning
confidence: 99%
“…Wang et al [142] 2012 Polymophisms of TNF-α are associated with the susceptibility to NAFLD Insulin resistance and hepatic inflammation are related Insulin signal transduction pathway does contribute to the progression of NAFLD…”
Section: Tnf-αmentioning
confidence: 99%
“…However, frequencies of variants -1031C and -863A were more prevalent in subjects with NASH in a different study (75). A meta-analysis evaluating polymorphisms in TNF-α confirmed the relationship of the -238 polymorphism with NAFLD, whereas the -308 polymorphism was not determined as a susceptible factor (76). Additionally, TNF-α G-308A, G-238A and C-863A polymorphisms are also related to HCC in Asians populations (77).…”
Section: Gene Polymorphisms In Mediators Of Related Cytokinesmentioning
confidence: 83%